Role of English Teachers in Inclusive Practices for Visually Impaired Students A Narrative Enquiry - Dhungana , Ankita; Gnawali , Laxman (Journal of NELTA, 2025)
This study aimed at examining the role of English teachers in supporting inclusive education for visually impaired (VI) learners in English Language Teaching (ELT). It adopted narrative inquiry as a research method and Lev Vygotsky’s social constructivist theory (1978) to investigate how teachers modify lesson plans, materials, and classroom settings to address the cognitive and affective needs of year (class) VI learners. Three themes emerged from the data obtained from the interviews, reflective journals, and classroom observations, namely, assistive technologies, emotional well-being and working with peers, and instruction of adaptive techniques. The findings suggest that faculty development, resource availability, and policies support creating inclusive classrooms for visually impaired students for their academic and emotional growth.